Curcumin Conjugated Gold Nanoclusters as Perspective Therapeutics for Diabetic Cardiomyopathy - Wei, Dong-zhuo; Li, Dan; Zheng, Dan-meng; An, Zhen-ni; Xing, Xue-jiao; Jiang, Ding-wen; Mei, Xi-fan; Liu, Chang (Frontiers in Chemistry, 2021)
Accumulation of lipids in the myocardium contributes to the development of cardiac dysfunctions and various chronic diseases, such as diabetic cardiomyopathy (DCM). Curcumin (Cur) can relieve lipid accumulation problems, but its efficiency is limited by poor water solubility and biocompatibility. Herein, gold nanoclusters (AuNCs) were used to improve the efficiency of Cur, and the conjugates Curcumin-AuNCs (AuCur) were developed. In the treatment of high-fat-induced myocardial cell damage, we found that AuCur could effectively reduce intracellular lipid accumulation, the increase of reactive oxygen species (ROS), the increase of mitochondrial division, and the increase of apoptosis compared with Cur. AuCur decreased the expression of the peroxisome proliferator-activated receptors-α subtype (PPARα), and the therapeutic effect of AuCur was canceled when the expression of PPARα was enhanced. For the above reasons, AuCur treated the toxic effect of high lipid on cardiomyocytes by regulating PPARα, providing a new idea and method for the treatment of DCM.